LEGAL STATUS OF THE NALCHIK SETTLEMENT HIGHLANDER JEWS (SECOND HALF OF THE 19th – EARLY 20th CENTURY) - MURZAKHANOV, Yu.I.; NORKINA, E.S. (Kavkazologiya, 2020)
The purpose of the article is to consider the legal status of mountain Jews in Kabardino-Balkaria from the moment of formation of the Nalchik mountain-Jewish settlement to the beginning of the twentieth century. The authors trace the change in the legal status of the Jewish population in the Caucasus, noting that as a result of many years of correspondence between representatives of the tsarist administration, mountain Jews were recognized as "Caucasian people", i.e. they had all the legal rights granted to the indigenous mountain population. Of great importance for determining the right of residence of Jews in the North Caucasus was the law « on the establishment and temporary residence of Jews in the Kuban and Terek regions "(1892)»; paragraph" b " of the second article was directly related to the mountain Jews. At the end of the XIX – beginning of the XX century, we can trace the spread of stereotypes that determine the practice of the authorities from Ashkenazi Jews to mountain Jews. Until 1917, the law regarding mountain Jews was not amended or supplemented, i.e. mountain Jews were not officially equalized in rights with the local population. In the context of the government's policy towards "other" Jews, the policy towards mountain Jews did not differ significantly.